Junger Westen '89. - Junger Westen '89 (Recklinghausen : Kunsthalle Recklinghausen, 1989)
Bier, Rolf ; Bräg, Daniel ; Brandmeier, Monika ; Damm, Ursula ; Dietzler, Georg ; Drebber, Magdalena ; Dudowitsch, Michael ; Fischer, Jochen ; Forster, Hannes ; Frick, Christoph ; Froelich, Dieter ; Fuhrmann, Frank ; Gerhards, Thomas ; Gerritz, Frank ; Haase, Tina ; Habegger, Daniel ; Hartung, Georg ; Hauf, Martin ; Heimbach, Klara ; Heinemann, Frank ; Hoegerl, Angelika ; Hoppe, Kristina ; Joeressen, Eva-Maria ; Kanne, Rita ; Kaun, Ralf Peter ; Karp, Thomas ; Kessl, Ulrike ; etc.
Junger Westen '89, Kunsthalle Recklinghausen, 8. Oktober bis 26. November 1989
boek